Evil - Karen Kilby (St Andrews Encyclopaedia of Theology, 2024)
Evil both is and is not a central part of the Christian theological vision. There is no equal and opposite to God, and no necessary or appropriate place for evil in God’s good creation. Nevertheless, creation is afflicted by evil: the divine response to evil is a central part of Christian faith and hope, and the human response to evil is a central part of Christian life and love. In modern thought, the ‘why’ of evil has come to particular prominence, with widespread attention to ‘the’ problem of evil and the question of theodicy. In the context of Christian theology, however, it is more helpful to think not of a single problem of evil but of a number of interlinking problems and questions. This article will first consider questions around the ‘what’ of evil: what kind of things count as evil, and what evil fundamentally is, i.e. the ontology of evil. It will then turn to a ‘how’ question: how God is understood to defeat evil, which from a theological point of view is the most significant question about evil, before finally taking up the more familiar ‘why’ question.